2021
DOI: 10.3389/fpls.2021.629089
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Response to Cadmium Exposure in Barley (Hordeum vulgare L.)

Abstract: Cadmium is an environmental pollutant with high toxicity that negatively affects plant growth and development. To understand the molecular mechanisms of plant response to cadmium stress, we have performed a genome-wide transcriptome analysis on barley plants treated with an increased concentration of cadmium. Differential gene expression analysis revealed 10,282 deregulated transcripts present in the roots and 7,104 in the shoots. Among them, we identified genes related to reactive oxygen species metabolism, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Studies on the SBP-box [ 19 ], WRKY [ 20 ], ABC [ 21 ], F-box [ 22 ], and SOD [ 23 ] gene family in barley have been successfully completed. Although the functions of several HMA proteins in barley have been reported [ 24 , 25 ], genome-wide analysis of the HvHMA family is lacking. In this study, the HvHMA gene family was genome-widely identified in barley, and the phylogenetic relationships, structural characteristics, physicochemical properties, chromosomal location, as well as the tissue expression of identified members were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the SBP-box [ 19 ], WRKY [ 20 ], ABC [ 21 ], F-box [ 22 ], and SOD [ 23 ] gene family in barley have been successfully completed. Although the functions of several HMA proteins in barley have been reported [ 24 , 25 ], genome-wide analysis of the HvHMA family is lacking. In this study, the HvHMA gene family was genome-widely identified in barley, and the phylogenetic relationships, structural characteristics, physicochemical properties, chromosomal location, as well as the tissue expression of identified members were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…HMA transporters also play an essential role in the loading of Cd in xylem vessels and phloem loading. Members of the HMA family have been identified in a variety of plant species, including A. thaliana ( Wong and Cobbett, 2009 ), rice ( Treesubsuntorn and Thiravetyan, 2019 ), barley ( Zhang et al., 2021 ), and wheat ( Kintlová et al., 2021 ). As ATPases, they can transport the cation from the cytosol into the xylem sap against its electrochemical gradient.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metal stress induces the activation of different mitogen-activated protein kinases (MAPKs) [120]. Kintlová et al [121] identified the HvPCR2 gene in barley as one of the most responsive genes to a Cd stimulus. Li et al [122] conducted a Populus × canadensis comparative transcriptomic study and found 35 TFs from 11 TF families in response to Cd stress, of which 16 were up-regulated while 19 were down-regulated.…”
Section: Role Of Transcriptome In Heavy Metalsmentioning
confidence: 99%